Hexokinase 2 Promotes Cell Growth and Tumor Formation Through the Raf/MEK/ERK Signaling Pathway in Cervical Cancer - Cui, Nan; Li, Lu; Feng, Qian; Ma, Hong-mei; Lei, Dan; Zheng, Peng-Sheng (Frontiers in Oncology, 2020)
Hexokinase 2 (HK2) is a member of the hexokinases (HK) that has been reported to be a key regulator during glucose metabolism linked to malignant growth in many types of cancers. In this study, stimulation of HK2 expression was observed in squamous cervical cancer (SCC) tissues, and HK2 expression promoted the proliferation of cervical cancer cells in vitro and tumor formation in vivo by accelerating cell cycle progression, upregulating cyclin A1 and downregulating p27 expression. Moreover, transcriptome sequencing analysis revealed that MAPK3 (ERK1) was upregulated in HK2-overexpressing HeLa cells. Further experiments found that the protein levels of p-Raf, p-MEK1/2, ERK1/2 and p-ERK1/2 were increased in HK2 over-expressing SiHa and HeLa cells. When ERK1/2 and p-ERK1/2 expression was blocked by an inhibitor (FR180204), reduced cyclin A1 expression was observed in HK2 overexpressing cells, with induced p27 expression and inhibited cell growth. Therefore, our data demonstrated that HK2 promoted the proliferation of cervical cancer cells by upregulating cyclin A1 and down-regulating p27 expression through the Raf/MEK/ERK signaling pathway.